Does gamification enhance the learning performance of postgraduate students? : a case study of management students in a multinational university - Manandhar, Sudeep; Igel, Barbara; Shah, Faiz H.; Zimmermann, Willi; Asian Institute of Technology Fellowship (2019)
This research aims to discover the enhance meant of learning performance through gamification of learning materials of past graduate students in School of Management. The research method is survey. Questionnaire have been collected and analyzed to find out that effects of gamification of a management subject has on the enhancement of learning on students. The research would contribute to understanding more about learning how gamification affects the process of learning and how learning is enhanced.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (MBA.) - Asian Institute of Technology, 2019
Keywords: Gamification -- Research